Wyniki leczenia zaćmy u dzieci i młodzieży będących pacjentami Kliniki Okulistycznej Uniwersytetu Medycznego w Poznaniu - Siwiec-Prościńska, Joanna; Gotz-Więckowska, Anna; Załęcki, Krzysztof; Kocięcki, Jarosław; Dmitriew, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Cataract is a leading course of a treatable blindness and serious visual impairment in children. Treatment, especially in one-sided cataract is a challenge and it is connected with the risk of complications. The decision to perform a surgery in older children with already coexisting amblyopia is not easy to make. The aim of our study was to present the effects of the cataract treatment in children between 3 and 18 years old, in the Ophthalmology Clinic in Poznań. Between 2006 and 2008, the surgery was done in 36 children (42 eyes). The data of those patients, e.g. the type and location of the cataract, accompanying disorders and visual acuity reached, were analyzed. In this group of patient 60% of children reached visual acuity equal to 0.5, and 24% of them full visual acuity. The way to prepare the patient to the surgery, the way to calculate the power of the intraocular lens to be implanted and the surgery technique will be discussed.